Back pain: development of diagnostic and treatment algorithms at the primary health care level of the Republic of Uzbekistan - Jalilovna, Halimova Dilrabo (International Journal of Psychosocial Rehabilitation, 2020)
The term "lower back pain" (LBP) is understood to mean pain, muscle tension and / or stiffness, localized in the back between the XII pair of ribs and lower gluteal folds with or without irradiation to the lower limb. LBP is a symptom, not a diagnosis, which was included in the ICD-10 as a registration category (M54.5 - “Lower back pain”) due to its high prevalence and frequent inability to establish a specific nosological cause of pain